Doença pulmonar obstrutiva crônica - Cavalcanti, Deborah Maciel [UNESP]; Alves Do Vale, Simone [UNESP]; Tanni, Suzana Erico [UNESP]; De Godoy, Irma [UNESP] (My University, 2004)
The chronic obstructive lung disease is reviewed with emphasys on its epidemiology and risk factors. The diagnosis, clinical aspects pulmonary, functional alterations and laboratorial findings are discussed. The treatment is also reviewed, based on the actual consensus, considering the following classes of approaches: bronchodilators, inhaled β-agonists, corticoids, methilxanthines, prolonged domiciliar-orygen therapy.
Chronic obstructive lung disease
Keywords: Chronic obstructive lung disease; Pulmonary diseases; alpha 1 antitrypsin; aminophylline; beta adrenergic receptor stimulating agent; bronchodilating agent; budesonide plus formoterol; cholinergic receptor blocking agent; corticosteroid; fenoterol; fenoterol plus ipratropium bromide; fluticasone propionate plus salmeterol; formoterol; ipratropium bromide; ipratropium bromide plus salbutamol sulfate; methylxanthine derivative; salbutamol; salmeterol; terbutaline; theophylline; tiotropium bromide; arterial gas; chronic obstructive lung disease; clinical feature; differential diagnosis; drug use; dyspnea; home care; human; laboratory test; lung function test; occupational exposure; oxygen therapy; prevalence; review; risk factor; smoking; spirometry; symptom; thorax radiography